Orexins and fear: implications for the treatment of anxiety disorders. Issue 9 (September 2015) - Flores, África; Saravia, Rocío; Maldonado, Rafael; Berrendero, Fernando
Highlights We review the role of orexins in the modulation of the neural circuits of fear. We describe the effects of orexin antagonists in animal models of anxiety disorders. We discuss the implications of this research for the treatment of anxiety disorders.